2018
DOI: 10.7287/peerj.preprints.27136v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rubber Hand Illusion does not arise from comparisons with internal body models: a new multisensory integration account of the sense of ownership

Abstract: Human body sense is surprisingly flexible – precisely administered multisensory stimulation may result in the illusion that an external object is part of one’s body. There seems to be a general consensus that there are certain top-down constraints on which objects may be incorporated: in particular, to-be-embodied objects should be structurally similar to a visual representation stored in an internal body model for a shift in one’s body image to occur. However, empirical evidence contradicts the body model hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
(201 reference statements)
0
2
0
Order By: Relevance
“…These considerations do not apply to another possibility of presenting artificial hands, provided by the development of virtual reality techniques. Virtual hands can be presented on a monitor (Farrer et al, 2003;IJsselsteijn et al, 2006;Ma and Hommel, 2013, 2018Ma et al, 2017;Wen et al, 2016), as 3D projection on a screen in an augmented reality set-up (Choi et al, 2016;Perez-Marcos et al, 2009;Sanchez-Vives et al, 2010;Slater et al, 2009), or within fully immersed VR environments using a head-mounted display (Fig. 2D; Bach et al, 2012;Bekrater-Bodmann et al, 2014;Nierula et al, 2017;Tieri et al, 2015).…”
Section: Type Of the Artificial Handmentioning
confidence: 99%
See 1 more Smart Citation
“…These considerations do not apply to another possibility of presenting artificial hands, provided by the development of virtual reality techniques. Virtual hands can be presented on a monitor (Farrer et al, 2003;IJsselsteijn et al, 2006;Ma and Hommel, 2013, 2018Ma et al, 2017;Wen et al, 2016), as 3D projection on a screen in an augmented reality set-up (Choi et al, 2016;Perez-Marcos et al, 2009;Sanchez-Vives et al, 2010;Slater et al, 2009), or within fully immersed VR environments using a head-mounted display (Fig. 2D; Bach et al, 2012;Bekrater-Bodmann et al, 2014;Nierula et al, 2017;Tieri et al, 2015).…”
Section: Type Of the Artificial Handmentioning
confidence: 99%
“…Hand similarity and anatomical plausibility has often been considered as a prerequisite for embodiment according to the idea that a hand or nonhand object is compared to an internal body model and multisensory integration only occurs with objects matching the body model (Tsakiris, 2010). It should be noted, however, that this idea is under debate and that it is possible that mere bottom-up sensory correlation can be sufficient to induce embodiment of non-corporeal objects at least under certain conditions (for a discussion see Kilteni et al, 2015;Litwin, 2018). For example, Guterstam et al (2013) reported that the artificial hand (whether anatomically plausible or not) does not have to be visible at all to induce a feeling of ownership (in this special case over a discrete volume of empty space).…”
Section: Choice Of Control Conditionsmentioning
confidence: 99%